2018
DOI: 10.1007/s11255-018-1954-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two detection systems for circulating tumor cells among patients with renal cell carcinoma

Abstract: We discovered that ISET is more suitable than the CSS for detecting CTCs in RCC patients. The presence of CTCs/CTMs in RCC patients correlated with higher TNM stages, suggesting that the presence of CTCs could be a prognostic marker in RCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
2
19
1
Order By: Relevance
“…RCC is reported to present with lower circulating tumor DNA (ctDNA) levels compared to other tumor entities (Smith et al, 2020), excluding it as a feasible diagnostic marker in RCC. Also, CTCs have not been established for clinical use in RCC diagnosis yet due to heterogenous surface marker expression (Bu et al, 2020), which makes an enrichment with the CellSearch TM system, the only FDA-approved CTC capture platform, difficult (Bai et al, 2018). Therefore, circulating ncRNAs might represent useful and easily available biomarkers in the diagnosis and treatment of RCC.…”
Section: Comparison To Current Standardsmentioning
confidence: 99%
“…RCC is reported to present with lower circulating tumor DNA (ctDNA) levels compared to other tumor entities (Smith et al, 2020), excluding it as a feasible diagnostic marker in RCC. Also, CTCs have not been established for clinical use in RCC diagnosis yet due to heterogenous surface marker expression (Bu et al, 2020), which makes an enrichment with the CellSearch TM system, the only FDA-approved CTC capture platform, difficult (Bai et al, 2018). Therefore, circulating ncRNAs might represent useful and easily available biomarkers in the diagnosis and treatment of RCC.…”
Section: Comparison To Current Standardsmentioning
confidence: 99%
“…Our ndings are not identical to previous studies which found that the TNM-Staging are related to the positive rate and level of CTCs. 23,24 One reason could be included that most patients were diagnosised with early clinical TNM Stage.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the CellSearch system, ISET has a higher detection rate for CTCs of RCC and more advantages in detecting renal cancer CTCs with low expression of EpCAM. 23 In recent studies, markers of G250 antigen 40,41 or CA9 combined with CD147 42 showed good prospects in the detection of CTCs in RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to various advantages, such as retention of cell morphology, antigen independence, and high sensitivity and specificity, membranous filter devices, for example, isolation by size of epithelial tumor cells (ISET) (Rarecells Diagnostics, Paris, France), have caught more attention in CTC researches. In a comparative study, Bai et al [47] estimated the clinical effect of CTCs by using CellSearch system and ISET devices among patients with renal cell carcinoma (RCC), discovering that ISET was more appropriate for RCC patients. CTCBIOPSY (Wuhan YZY Medical Science and Technology Co., Ltd., China) is a commercial one-step ISET device which could complete automatic detection and identification within 10 min [48] .…”
Section: Size-based Ctc Isolationmentioning
confidence: 99%